Risk factors and outcome of malformations of gastrointestinal tract in neonates in a tertiary care center in India - Shobhna Gupta; Krishan Kumar; Novy Gupte; Deepak Bagga; R. M. Pandey; Harish Chellani (Indian Journal of Child Health, 2021)
Objective: The objective of the study was to determine the prevalence and associated risk factors of malformations of the gastrointestinal tract (MGIT) in neonates in a tertiary care hospital. Methods: We conducted a prospective, observational, case–control study on all intramural neonates till discharge/outcome for 1 year. Babies with MGIT diagnosed antenatally or postnatally were taken as cases and two consecutively born healthy babies were taken as controls. Results: Out of 25,116 live births, there were 41 cases of MGIT with a prevalence of 1.63 per 1000 live births. Tracheoesophageal fistula was the most common (39.02%), followed by anal atresia (24.39 %), esophageal atresia (9.46%), and mesenteric cyst (7.31%). Antenatally and postnatally, 16 (39.1%) and 25 (60.9%) cases were diagnosed, respectively. A significant association was observed between MGIT and lack of periconceptional iron/folic acid supplementation, birth weight <2.5 kg, maternal age >30 years, low socioeconomic profile, consanguinity, febrile illness in first trimester, and gender. The average time to onset of first feed and mean duration of hospital stay in babies with MGIT were 7 days and 14 days, respectively. Conclusion: Most MGIT can be diagnosed clinically and radiologically before/soon after birth and have a good outcome with timely surgical intervention. Pre-pregnancy counseling for periconceptional folic acid supplementation with screening ultrasonography, appropriate follow-up, and referral system should be developed for the management of these cases. A coordinated multidisciplinary approach for prevention, management, and rehabilitation of affected babies is required.